Morphological and Molecular Identification of Holothuria (Merthensiothuria) leucospilota and Stichopus horrens from Pangkor Island, Malaysia - Kamarul Rahim Kamarudin; Maryam Mohamed Rehan (Tropical Life Sciences Research, 2015)
This preliminary study aimed to identify a commercial gamat species, Stichopus horrens Selenka, 1867, and a timun laut species, Holothuria (Mertensiothuria) leucospilota (Brandt, 1835), from Pangkor Island, Perak, Malaysia, employing morphological techniques based on the shape of the ossicles and molecular techniques based on the cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene. In Malaysia, a gamat is defined as a sea cucumber species of the family Stichopodidae with medicinal value, and timun laut refers to non-gamat species. S. horrens is very popular on Pangkor Island as a main ingredient in the traditional production of air gamat and minyak gamat, while H. leucospilota is the most abundant species in Malaysia. In contrast to previous studies, internal body parts (the respiratory tree and gastrointestine) were examined in this study to obtain better inferences based on morphology. The results showed that there were no ossicles present in the gastrointestine of H. leucospilota, and this characteristic is suggested as a unique diagnostic marker for the timun laut species. In addition, the presence of Y-shaped rods in the respiratory tree of S. horrens subsequently supported the potential to use internal body parts to identify the gamat species. Phylogenetic analysis of the COI mtDNA gene of the sea cucumber specimens using the neighbour-joining method and maximum likelihood methods further confirmed the species status of H. leucospilota and S. horrens from Pangkor Island, Perak, Malaysia. The COI mtDNA gene sequences were registered with GenBank, National Center for Biotechnology Information (NCBI), US National Library of Medicine (GenBank accession no.: KC405565-KC405568). Although additional specimens from various localities will be required to produce more conclusive results, the current findings provide better insight into the importance of complementary approaches involving morphological and molecular techniques in the identification of the two Malaysian sea cucumber species. Kajian awal ini bertujuan untuk mengenalpasti satu spesies komersil gamat iaitu Stichopus horrens Selenka, 1867 dan satu spesies timun laut iaitu Holothuria (Mertensiothuria) leucospilota (Brandt, 1835) dari Pulau Pangkor, Perak, Malaysia dengan mengaplikasikan teknik-teknik morfologi berdasarkan bentuk-bentuk osikel dan teknik-teknik molekul menggunakan gen sitokrom c osidasi I (COI) mitokondria DNA (mtDNA). Di Malaysia, gamat didefinisikan sebagai spesies timun laut daripada famili Stichopodidae yang memiliki nilai-nilai perubatan manakala timun laut dirujukkan kepada spesies bukan gamat. Spesies S. horrens adalah amat popular di Pulau Pangkor sebagai bahan utama dalam penghasilan air gamat dan minyak gamat secara tradisional manakala H. leucospilota merupakan spesies paling dominan di Malaysia. Berbeza dengan kajian-kajian sebelum ini, bahagian dalaman tubuh iaitu pohon respirasi dan gastrousus telah disertakan dalam kajian ini untuk mendapatkan kesimpulan yang lebih baik berdasarkan morfologi. Keputusan-keputusan menunjukkan tiada osikel telah hadir di dalam gastrousus H. leucospilota dan ciri tersebut dicadangkan sebagai penanda diagnostik yang unik untuk spesies timun laut tersebut. Di samping itu, kehadiran rod berbentuk Y di dalam pohon respirasi S. horrens seterusnya menyokong potensi bahagian dalaman tubuh untuk mengenalpasti spesies gamat tersebut. Selanjutnya, analisis-analisis filogenetik gen COI mtDNA spesimen-spesimen timun laut tersebut menggunakan kaedah hubungkait jiran dan kaedah persamaan maksimum seterusnya mengesahkan status spesies H. leucospilota dan S. horrens dari Pulau Pangkor, Perak, Malaysia. Jujukan-jujukan gen COI mtDNA tersebut telah didaftarkan dengan GenBank, National Center for Biotechnology Information (NCBI), US National Library of Medicine (no. akses GenBank: KC405565-KC405568). Walaupun lebih banyak spesimen dari pelbagai lokasi diperlukan untuk menghasilkan keputusan-keputusan muktamad yang lebih baik, penemuan-penemuan semasa telah memberi gambaran yang lebih baik tentang kepentingan pendekatan-pendekatan yang saling lengkap-melengkapi iaitu teknik-teknik morfologi dan molekul dalam pengenalpastian kedua-dua spesies timun laut Malaysia tersebut.